Analisis Strategi Penguatan Kelembagaan Masyarakat Dalam Program Rehabilitasi Hutan dan Lahan (RHL) di Desa Sumberejo, Kabupaten Wonogiri, Wilayah Kerja BPDAS Solo - Mita Nur Hidayati; Aziz Akbar Mukasyaf; Danardono; Afif Ari Wibowo (Mataram University, 2026)
The success of the Forest and Land Rehabilitation (RHL) Program is influenced by the level of community participation and institutional capacity at each stage of implementation. This study aims to analyze the level of community institutional participation, identify internal and external factors affecting these institutions, and formulate strategies to strengthen community institutions within the RHL Program in Sumberejo Village, Wonogiri Regency (under the jurisdiction of BPDAS Solo). A descriptive approach employing both quantitative and qualitative methods was used. Data were collected through observation, interviews, questionnaires, and document review involving 40 members of the Forest Farmer Group selected via random sampling, while key informants were chosen through purposive sampling. Data analysis utilized a Likert scale, IFAS-EFAS matrices, and SWOT analysis. The results indicate that community institutional participation falls into the